REVITALISASI ARSITEKTUR DI TAMAN LAPANGAN BANTENG - Fadiliawan, Calvin; Ayu Oktaviani (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2020)
n revitalizing a historic area, we need to know what aspects need to be considered in revitalizing.Revitalizing a historic area from an ordinary area is very different because in a historic area it is necessaryand an obligation to maintain some of the historical values that have existed and have occurred in the areaso as not to lose the historical value that has occurred in the area. And the Banteng Field Park is alsocurrently the flagship park of the community in the Special Capital Region (DKI) Jakarta for sports,recreation, watching cultural arts performances and spending free time there because it has a large enougharea and also has a good and sustainable architectural concept in was designed and built by the DKIJakarta Provincial Government and was revitalized in 2017. After revitalizing the park, it looks new andhas a good and beautiful architecture that raises the intention of the surrounding community, especially thepeople of Jakarta, to visit and also spend time there. Therefore, the author wants to examine more deeplyan architectural revitalization in the Banteng Field Park which has quite a lot of history since the absenceof the Republic of Indonesia until now, with various research methodologies available for conductingresearch and studies, especially for making architectural journals